2014
DOI: 10.1063/1.4896774
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationary dynamics in the bouncing ball: A wavelet perspective

Abstract: The non-stationary dynamics of a bouncing ball, comprising both periodic as well as chaotic behavior, is studied through wavelet transform. The multi-scale characterization of the time series displays clear signatures of self-similarity, complex scaling behavior, and periodicity. Self-similar behavior is quantified by the generalized Hurst exponent, obtained through both wavelet based multi-fractal detrended fluctuation analysis and Fourier methods. The scale dependent variable window size of the wavelets aptl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…This is the frequency where the transfer of power occurs at the boundary of low frequency alpha and beta waves that becomes prominent for patients during seizure. We also analyzed the energy transfer phenomenon [37,38], by reconstructing the time series from the Fourier space, excluding the UPO range 8-14Hz for use in the Heisenberg model. Once these characteristic frequencies are removed at 8-14Hz in UPO range, the universal scale free behavior is manifest in the Heisenberg model.…”
Section: Resultsmentioning
confidence: 99%
“…This is the frequency where the transfer of power occurs at the boundary of low frequency alpha and beta waves that becomes prominent for patients during seizure. We also analyzed the energy transfer phenomenon [37,38], by reconstructing the time series from the Fourier space, excluding the UPO range 8-14Hz for use in the Heisenberg model. Once these characteristic frequencies are removed at 8-14Hz in UPO range, the universal scale free behavior is manifest in the Heisenberg model.…”
Section: Resultsmentioning
confidence: 99%
“…This is the frequency where the transfer of power occurs at the boundary of low frequency alpha and beta waves that becomes prominent for patients during seizure. We also analysed the energy transfer phenomenon [36,37], by reconstructing the time series from the Fourier space, excluding the UPO range 8-14Hz for use in the Heisenberg model. Once these characteristic frequencies are removed at 8-14Hz in UPO range, the universal scale free behaviour is manifest in the Heisenberg model.…”
Section: Resultsmentioning
confidence: 99%
“…A careful study of CWT coefficients, as shown in Fig.21(a), (b) and (c), reveal that BSE and NYSE are moving in tandem, except when one of them is non-periodic, revealing a transition period leading to an unstable regime [24,41]. Fig.21(c), exhibiting the degree of integration of BSE.…”
Section: Comparing the Coefficients Of Bse And Nysementioning
confidence: 95%
“…As is well known, stock prices are affected by a plethora of factors, the dynamics of which do not get easily revealed in the time series plot of the stock prices [23]. A better understanding of the market dynamics is obtained through phase-space analysis, through the study of the returns as a function of the price indexes, akin to the velocity-trajectory plots in particle dynamics [24,25]. The phase space plots shown in Fig.4, clearly reveal periodic and structured variations, both in the short and long time scales.…”
Section: Datamentioning
confidence: 99%